U źródeł polskiej sowietologii. Publicystyka polityczna Józefa Mackiewicza w okresie Drugiej Rzeczypospolitej - Łukomski, Grzegorz (Studia Europaea Gnesnensia, 2010)
Józef Mackiewicz, as a writer for “Słowo”, a newspaper published in Vilnius, was particularly interested in communist ideology. He should be considered as the father of the Polish school of sovietology. The article analyses Mackiewicz’s way of thinking in the matters of communism and the Soviet system.